(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Transdermal nicotine patches have been used in smoking cessation therapy, suggested for the treatment of skin disorders with eosinophilic infiltration and have been found to improve attention performance in patients with Alzheimer's disease and age-associated memory impairment. However, skin irritation with extended patch use is still a problem. The aim of this work was to develop a simple to prepare liquid crystalline system containing vitamin E TPGS that would be able to control nicotine delivery and reduce irritation and sensitization problems. The liquid crystalline phases were macroscopically characterized by visual analysis and examined microscopically under a polarized light microscope. Topical and transdermal delivery of nicotine were investigated in vitro using porcine ear skin mounted on a Franz diffusion cell. Nicotine skin permeation from the developed cubic phase followed zero-order kinetics (r = 0.993) and was significantly enhanced after 12 h when compared to the control formulation (nicotine solution) (p < 0.05) (138.86 ± 20.44 and 64.91 ± 4.06 μg/cm2, respectively). Cubic phase was also able to target viable skin layers in comparison to control solution (8.18 ± 1.89 and 2.63 ± 2.51 μg/cm2, respectively). Further studies to evaluate skin sensitization and irritation are now necessary.